MENYELAMI KONSEP KESATUAN USAHA DALAM TEORI-TEORI AKUNTANSI - Zulkarim Salampessy; Maria Juneferstina (Jurnal Administrasi Terapan, 2023)
This research was conducted with the aim of explaining the existence of the business entity concept contained in various accounting theories. Researchers place library research in researching and examining the thoughts of experts scattered in articles, books and other documents, about the concept of business units contained in accounting theories. The results of the research show that the concept of business entity contained in; The first is the proprietary theory, namely business actors (entrepreneurship) as owners (proprietors) who are integrated with the company are seen as having an interest in economic activity and are entitled to company profits. Second, entity theory is a corporation as a form of company in which the owner is separate from the company and is represented by management. Third, enterprise theory is the determination and recognition of other parties outside the shareholders (owners of capital) as stakeholders who are seen as having an interest in the company's economic activities. For example management, employees, creditors, suppliers, government, society, and the natural environment. Fourth, sharia enterprise theory is to accommodate the social aspects (stakeholders) that underlie accounting principles and techniques that reflect the values of fairness, truth, honesty, trust, and corporate responsibility. Keywords: Business Entity, Accounting Theory, proprietary theory, entity theory, enterprise theory, shariah enterprise theory